Pengaruh Pengawasan Terhadap Disiplin Kerja Karyawan Pada PT. “ABC” Pekanbaru - Risman, Risman (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
The purpose of this study was to determine the effect of supervision on employee work discipline at PT. ABC Pekanbaru. To achieve this goal, a study was conducted using a sample of 31 people, using the census method. Methods of data analysis using simple linear regression. Based on the results of partial t-test testing, it was found that supervision had a significant effect on employee work discipline at PT. ABC Pekanbaru, this is proven based on the t test found that t-count is greater than t-table (10,637 > 2,023). The magnitude of the influence of the supervision variable on the employee work discipline variable is 0.744 (74.4%) this is proven based on the results of the determination test where an R2 value of 0.744 is obtained. Recommendations that can be submitted are expected that the company will carry out careful supervision by the leadership because this gets the lowest response from respondents.